2019
DOI: 10.1002/14651858.cd012943.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating neuropathic pain in people with sickle cell disease

Abstract: Interventions for treating neuropathic pain in people with sickle cell disease (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…20 Examples of medications that have strong supporting evidence as first-line treatment of neuropathic and other pain include tricyclic antidepressants, serotonin noradrenaline reuptake inhibitors, selective serotonin reuptake inhibitors, and gabapentinoids such as gabapentin and pregabalin. 26 A recent systematic review by Asnani et al 27 found that just 1 randomized neuropathic drug clinical trial has been conducted in patients with SCD with only 22 subjects. 28 More trials are needed to support the efficacy of neuropathic medication in treating chronic pain in SCD.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…20 Examples of medications that have strong supporting evidence as first-line treatment of neuropathic and other pain include tricyclic antidepressants, serotonin noradrenaline reuptake inhibitors, selective serotonin reuptake inhibitors, and gabapentinoids such as gabapentin and pregabalin. 26 A recent systematic review by Asnani et al 27 found that just 1 randomized neuropathic drug clinical trial has been conducted in patients with SCD with only 22 subjects. 28 More trials are needed to support the efficacy of neuropathic medication in treating chronic pain in SCD.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…As the model of pain in SCD grows more complex, so must the management approach. The rate at which patients receive medications targeting NP in particular as a cause of chronic pain lags far behind its likely prevalence among patients with SCD [ 4 , 5 , 39 ]. The recent guidelines from the American Society of Hematology for the treatment of SCD‐associated chronic pain include the use of several medications recommended for NP treatment in the broader pain literature, but the recommendations are based almost entirely on data from other disease processes due to the lack of clinical trials targeting NP in SCD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Waldfogel and collaborators (2017) found 10 studies of low quality of evidence involving pregabalin and quality of life, of which 4 show significant improvement, while 6 show no improvement compared to the placebo group according to the SF-36 (Waldfogel et al, 2017). In the review carried out by Asnani et al (2019) it was shown that the quality of life of patients using pregabalin did not improve compared to the placebo group according to the SF-36, however in three months of followup, a small improvement could be noted in 7 of 8 SF-36 domains post-intervention in the intervention group compared to the placebo group, all via the quality of evidence is very low (Asnani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%